Toolbox for sustainable rehabilitation of rangelands in arid environments - CGIAR Research Program on Livestock (2020)
The first version is ready (will be refined through editing and layout). the final version will be completed in 2021. More sustainable rangeland management practices were added in 2020. More visibility for the SRM tool was done through Participants in the national tree event in Tunis